The Impact Of Sex, Origin, And Attitude On The Phonological Accommodation Among University Students In Irbid - Rifai, Marashdeh Mohammed Mahmoud (2024)
Phonological accommodation, or phonological convergence, describes the phenomenon where individuals adjust their speech styles to align more closely with their interlocutor's speech. This thesis delves into the impact of three social variables— origin, sex, and attitudes—on phonological accommodation, using the phonological variables (q), (D), (Θ), and (ð) as indicators of salience to examine this phenomenon. A total of 60 participants were selected using a quota sampling method, and data was gathered through a structured questionnaire that is divided into four sections: demographic, identification, phonological variables use, and attitude. and in-depth interviews with twelve respondents, evenly distributed by origin and sex. The questionnaire and interview data were analyzed descriptively, while the attitude section of the questionnaire used Likert scale that rates from strongly agree (1) to strongly disagree (5). The findings revealed distinct patterns of phonological convergence. Females from rural Palestinian backgrounds showed complete convergence to the urban speech form, whereas their Horani counterparts exhibited partial convergence to the urban variety. Males from rural Palestinian backgrounds tended to adopt the Horani local variant of the (Q) variable, while remaining conservative with the other phonological variables.